Evaluation of the interplay between NASH and HFpEF in varied murine age groups. (10th June 2022) - Kucsera, D; Sayour, N V; Ruppert, M; Radovits, T; Fabian, A; Kovacs, A; Ferdinandy, P; Varga, ZV
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 Research and Innovation Programme, grant agreement no. 739593 New National Excellence Program of the Ministry of Human Capacities (ÚNKP-21-3-II) Introduction: Heart failure with preserved ejection fraction (HFpEF) is characterized by diastolic dysfunction, left ventricular hypertrophy, left atrial enlargement and increased serum levels of NT-pro-BNP. HFpEF accounts for 50% of heart failure cases, and typically develops in patients with metabolic comorbidities. Non-alcoholic fatty liver disease and subsequent steatohepatitis (NAFLD, NASH) is the most common chronic liver disease developing due to obesity. Although clinical/epidemiological data exists in humans showing that NASH may lead to cardiac dysfunction per se, experimental data in this regard is lacking. Purpose: We aimed to evaluate whether NASH is an independent factor of cardiac dysfunction and to investigate the age-dependent effects of NASH on cardiac function. Methods: Middle aged (10 months old) and aged (24 months old) C57Bl/6J mice were fed either control diet or Choline Deficient (CDAA) diet over a period of eight weeks. Young (2 months old) mice were used as a control. Before termination, echocardiography was performed. Upon termination, organs were isolated for further analysis. Results: CDAA diet lead to the development of NASH in both age groups, without inducing weight gain, allowing us to investigate the direct effects of NASH on cardiac function. Left ventricular end-diastolic volume (EDV) was increased in aged animals, compared to young and middle aged animals, suggesting increased ventricular pressure. Aged animals were characterized by increased posterior wall thickness (PWT) during diastole and by increased LV mass, indicating left ventricular hypertrophy. Assessment of ejection fraction showed an age-dependent decline. Pulse wave and tissue Doppler measurements showed no difference in E/e' ratio between the groups. However, strain analysis showed that diastolic dysfunction developed only in aged mice due to NASH. Conclusion: We conclude that there were no observed changes in cardiac diastolic function due to NASH when using standard echocardiographic evaluation; however, the more sensitive method of strain analysis with 2D speckle tracking was able to show evidence of diastolic dysfunction due to NASH in aging animals.